A força da pena: um estudo acerca da valorização do bacharel em Direito nas relações políticas dos sul-riograndenses: Pelotas e Alegrete (1850- 1870) - Maia, Leonardo Poltozi (2016)
The Master's thesis entitled "The power of the pen: a study on the valuation of Law Degree in political relations of Rio Grande Sul: Pelotas and Alegrete (1850- 1870)", developed in the Research Line "Frontier, Politics and society "of the Graduate Program in History at the Federal University of Santa Maria - UFSM, which featured Master's scholarship Program Social Demand FAPERGS/CAPES, aims to analyze the situation about the Bachelor valuation process in law and so his knowledge in political discourse and its post-formed features in the second half of the nineteenth century, analyzing more specifically the municipalities of Alegrete and Pelotas in the period between 1850 1870. This historical approach is justified in the sense of the social, political and legal Sul-rio-grandense to be a process of change after Farroupilha Revolution (1835-1845), where the "penalty" replaced the "sword", when it comes to defending their provincial interests, or interests of the elites in relation to the Imperial government. These elites were searching the intellectual capital to maintain or achieve the political capital of the time. In this sense, we seek to understand the insertion of Bachelor of Laws in the bureaucratic sphere in the process of formation and consolidation of the post-independence Brazilian state through an analysis of the organization of the bureaucratic system that is created. Besides presenting some bachelors paths listed for this thesis, in the sense that the legal training to the achievement of political and bureaucratic positions of prominence in the nineteenth century was almost always advantageous.